Enantioselective Strecker reaction of aldimines using potassium cyanide catalyzed by a recyclable macrocyclic V(v) salen complex. Issue 121 (23rd November 2015) - Saravanan, S.; Khan, Noor-ul H.; Jakhar, Ajay; Ansari, Amamudin; Kureshy, Rukhsana I.; Abdi, Sayed H. R.; Kumar, Gaurav
Abstract : Chiral dimeric V(v ) salen complexes have been synthesized and used as catalysts for asymmetric Strecker reaction of N -benzylimines using both KCN to produce chiral α-amino nitrile. The catalyst was recycled upto five times without loss in its activity. Abstract : A chiral dimeric macrocyclic V(v ) salen complex based on a chiral macrocyclic salen ligand derived from 1 R, 2 R -(−) diaminocyclohexane with trigol bisaldehyde was synthesized and evaluated as an efficient catalyst (5 mol%) for asymmetric addition of potassium cyanide and trimethylsilyl cyanide to various N -benzylimines at −20 °C. The dimeric chiral macrocyclic salen complex was found to be an efficient recyclable catalyst to give a high yield (91%) of α-aminonitrile and high chiral induction (ee up to 99%) in the case of 2-methoxy substituted N -benzylimines in 16 h. The catalytic system worked well with both organic and inorganic cyanide sources and the catalyst was recycled up to five cycles with retention of enantioselectivity. Based on NMR investigation and kinetics a probable mechanism was proposed for the catalytic enantioselective Strecker reaction.